Implantación de contabilidad comercial en el almacén de electrodomésticos López, de la ciudad de Orellana - Sacha, periodo: enero a febrero 2015 - Tapia Ponce, Jessica Marisela (2016)
This thesis topic "IMPLEMENTATION OF BUSINESS ACCOUNTING IN STORE APPLIANCES LOPEZ, Orellana CITY - Sacha PERIOD: January to February 2015", it has been developed according to the needs of the warehouse according to information provided by the owner , which has provided insight into operations, movements and weaknesses of the business, research is conducted to apply knowledge to help improve the operation thereof, and also, why is a requirement to obtain the title Engineer Accounting and Auditing CPA, as it is my career. This research work was carried out with the purpose of determining the actual movements of each account and the economic situation of the same, by fulfilling the objectives proposed at the beginning of the investigation, was compiled and correctly ordered source documentation, it was conducted lifting the initial inventory, goods account was regulated by applying the perpetual inventory system, the plan accounts and manual was developed and the entire accounting process was developed by the State of baseline to the Financial Statements. At the conclusion of the execution of Implementation of Commercial Accounting in the store, the owner managed to verify the utility obtained at the end of this fiscal year, managed to identify accurately the real values of income and expenses, it could also analyze this exercise helped to improve economic business, it is recommended to continue performing daily accounting records, in order to be able to get the always current, clear, accurate, timely and reliable information, as this will help to take corrective decisions.